2021
DOI: 10.1002/wer.1628
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical oxidation of chloramphenicol with lead dioxide–surfactant composites

Abstract: The PbO2–2 wt.% sodium dodecyl sulfate composite formed from methanesulfonate electrolyte consists of 93.1% of α‐phase PbO2 in contrast to the similar one synthesized from nitrate electrolyte, which contains 73.3% of β phase. The electrocatalytic activity of the obtained composites in the oxygen evolution reaction and oxidation of chloramphenicol was investigated. It was found that the Tafel slope significantly exceeds the theoretical value, which indicates a decrease in the degree of filling of the electrode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Electrodeposition process of PbO A large number of studies have shown that the addition of surfactants can increase the deposition of PbO 2 , however, the electrochemical behavior and deposition mechanism in the deposition process need to be further discussed. [43][44][45][46][47] On this basis, cyclic voltammetry (CV) and chronoamperometry (CA) tests were carried out in Pb(NO 3 ) 2 system with glassy carbon electrode to study the electrodeposition process of PbO 2 , then OP-10 was added to the solution to further explore the effect of OP-10 on the electrodeposition process of PbO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Electrodeposition process of PbO A large number of studies have shown that the addition of surfactants can increase the deposition of PbO 2 , however, the electrochemical behavior and deposition mechanism in the deposition process need to be further discussed. [43][44][45][46][47] On this basis, cyclic voltammetry (CV) and chronoamperometry (CA) tests were carried out in Pb(NO 3 ) 2 system with glassy carbon electrode to study the electrodeposition process of PbO 2 , then OP-10 was added to the solution to further explore the effect of OP-10 on the electrodeposition process of PbO 2 .…”
Section: Resultsmentioning
confidence: 99%